If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
3*x-(x/5)-(7/10) = x/10+4 // - x/10+4
3*x-(x/5)-(x/10)-(7/10)-4 = 0
3*x-(x/5)-(x/10)-7/10-4 = 0
27/10*x-47/10 = 0 // + 47/10
27/10*x = 47/10 // : 27/10
x = 47/10/27/10
x = 47/27
x = 47/27
| -2/7r+2r=1/2r+7/2 | | -5(x+3)=-50 | | 5-1.11=x | | 2+9/(x-6) | | -6x=174 | | (5x^2-2x-4)+(3x^2-x+6)= | | 4.3y=21.5 | | k=-61/7^4/21 | | 235/100 | | 0.1t=3 | | (3x-5)/7=0 | | 12x+4y=9 | | (3x-5)/7 | | h=6+26t-16t^2 | | 9=28-4y | | 8y-10=5y+5 | | a=-1/2^1/3 | | 2.93/1000=x | | -4.9t^2+27.5t+8.2=0 | | M+9=-2 | | g=41/4(21/3) | | m^2-9/2m=3/2 | | m^2-9/2m=3/2 | | -4.9t^2+24.5t+8.8=0 | | c=10/33(42/5) | | y2+3/2y=3 | | t=3/2(-4/9) | | 41-7y=8 | | 5x^2+6x-12=0 | | j=7/5+(-87/8) | | 2x-4(11-3x)=-2 | | 3x+4/10=x/5 |